2019
DOI: 10.37358/rc.19.5.7223
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Changes and Risk Factors in the Prognosis of Antibiotics Susceptibility in Urinary Tract Infections

Abstract: The aim of our study was evaluation of prevalence of uncomplicated and complicated urinary tract infections (UTIs) among patients with UTIs associated with Gram - negative bacteria and analysis of prognostic risk factors in complicated UTIs. Weretrospectivelyanalyzed the medical records of inpatients with diagnosis of UTI based on clinical, biological and microbiological assay. Susceptibility tests for different antimicrobial categories were performed. Risk factors in complicated UTIs were correlated with path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The significant per capita antibiotic consumption in Romania, coupled with ineffective measures in terms of intra-hospital infection prophylaxis, is the basis for the increased rates of AMR in this geographical area. Both national and international multicenter studies support this hypothesis, mentioning that for some antimicrobials, epidemiological alerts have even been issued due to their alarming resistance rate [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 92%
“…The significant per capita antibiotic consumption in Romania, coupled with ineffective measures in terms of intra-hospital infection prophylaxis, is the basis for the increased rates of AMR in this geographical area. Both national and international multicenter studies support this hypothesis, mentioning that for some antimicrobials, epidemiological alerts have even been issued due to their alarming resistance rate [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 92%
“…(34.5%) and Vata et al[17] (17.7%). We also found that catheterized patients with age ≤40 years of age are more prone to UTI 31/247 (12%).…”
mentioning
confidence: 87%
“…Empirical antibacterial therapeutic approach depends on the severity of disease (e.g. uncomplicated vs. complicated UTIs), the spectrum of the possible pathogens and the local resistance patterns (8). The most frequent pathogens involved are from Enterobacteriaceae group, mainly E. coli and Klebsiella pneumonia (9).…”
Section: Introductionmentioning
confidence: 99%